Women smallholder agricultural farmers' views on gender equility and the role of informal agricultural associations in the Catembe district, Mozambique - De Kock, Karen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA) -- University of Stellenbosch, 2007.